Ectopic overexpression of mulberry MnT5H2 enhances melatonin production and salt tolerance in tobacco - Zhu, Baozhong; Zheng, Sha; Fan, Wei; Zhang, Meirong; Xia, Zhongqiang; Chen, Xuefei; Zhao, Aichun (Frontiers in Plant Science, 2022)
Soil salinization severely inhibits plant growth and has become one of the major limiting factors for global agricultural production. Melatonin (N-acetyl-5-methoxytryptamine) plays an important role in regulating plant growth and development and in responding to abiotic stresses. Tryptamine-5-hydroxylase (T5H) is an enzyme essential for the biosynthesis of melatonin in plants. Previous studies have identified the gene MnT5H for melatonin synthesis in mulberry (Morus notabilis), but the role of this gene in response to salinity stress in mulberry is remain unclear. In this study, we ectopically overexpressed MnT5H2 in tobacco (Nicotiana tabacum L.) and treated it with NaCl solutions. Compared to wild-type (WT), melatonin content was significantly increased in the overexpression-MnT5H2 tobacco. Under salt stress, the expression of NtCAT, NtSOD, and NtERD10C and activity of catalase (CAT), peroxidase (POD), and the content of proline (Pro) in the transgenic lines were significantly higher than that in WT. The Malondialdehyde (MDA) content in transgenic tobacco was significantly lower than that of WT. Furthermore, transgenic tobacco seedlings exhibited faster growth in media with NaCl. This study reveals the changes of melatonin and related substance content in MnT5H2-overexpressing tobacco ultimately lead to improve the salt tolerance of transgenic tobacco, and also provides a new target gene for breeding plant resistance to salt.